The politics of memory and commemoration in the post-apartheid era: a case study of 32-Battalion - Heywood, Julia (My University, 2015)
This research report looks at the politics of memory, commemoration and representation in the new South Africa with a focus on 32-Battalion. The research draws on interviews and testimonies of ex-SADF soldiers who were members of the unit and unpacks how when considering memory and remembering, a multitude of viewpoints emerge. Factors such as the impact of the ideological transition from apartheid to democracy and the resultant impact on ex-SADF soldiers as well as the reshaping of the country’s official history which has been shaped to suit the current political climate, are considered. The research reflects on how these political processes which include exclusions of unwanted histories have affected nation building in South Africa post 1994.
A research report submitted by the Wits School of Arts, Film and Television Department, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters in Film and Television. Johannesburg 2015
Keywords: South Africa--Army--Battalion, 32; History--Psychological aspects; Recollection (Psychology); Collective memory; Special forces (Military science)--South Africa; Angola--History--South African Invasion, 1975-1976; Angola--History--South African Incursions, 1978-1990